Formulation of the homological functors of some Bieberbach groups with dihedral point group - Wan Nor Farhana Wan Mohd Fauzi (Tanjong Malim, 2015)
Formulation of the homological functors of some Bieberbach groups with dihedral point group by Wan Nor Farhana Wan Mohd Fauzi